PKM KELOMPOK USAHA BERSAMA (KUBE) ANEKA CEMILAN KHAS MELAYU DI KEL. TAMPAN KEC. PAYUNG SEKAKI KOTA PEKANBARU - Zayyinul Hayati Zen; Denny Astrie Anggraini; Yohanes Yohanes (LPPM UMRI, 2018)
Tampan Village had several Joint Business Groups as known as KUBE. Two of them were KUBE Flower Creative and AlifDifa. This KUBE produces various of Malay snacks. The featured products from these KUBE were Bolu Kemojo and Bolu Ubi Pelangi. Some problems that were found from KUBE were: production capability was low due to manual work using simple equipment with own labor, limited capital and access, there was bad financial management, product packaging were simple and not attractive, and management of group organizations in the management of KUBE didn’t run yet. Some activities carried out: Socialization with mothers of KUBE members. From the beginning of two KUBE, 4 KUBE are now being gathered under the auspices of the Dapur AlifDifa. Dapur AlifDifa was built as a place for development and products of KUBE members. Successful activities include mentoring increased knowledge of human resources about the snack food industry, development of attractive logo, packaging designs, and professional business management. Assistance for improving the promotion media process and development in the website www.selerariau.com. With the effort of mentoring and training partners, the results of Bolu Kemojo and Bolu Ubi Pelangi production of partners began to be known, and the profit increased.